A study on influence of different signal peptides on anti-tumor effect of chimeric antigen receptor (CAR) T cells - LI Fan, ZHANG Qinxing, TONG Xiangwen, TIAN Gaohui, GU Lixing, XU Yao (Zhongguo aizheng zazhi, 2022)
Background and purpose: Signal peptide (SP) is a short peptide chain at the N-terminal of precursor protein, which can regulate the folding and transfer of precursor protein and plays an important role in protein secretion. In recent years, significant breakthroughs have been made in the treatment of leukemia with CD19-targeted chimeric antigen receptor (CAR) T cells, and many achievements have been reported in the intracellular domain modification of CAR structure, while the N-terminal SP of scFv presents less progress. The purpose of this study was to investigate the CD19-CAR expression of four different SP on the surface of T cells and their effect on the killing of CD19+ target cells. Methods: The CAR vectors containing four different SP (SP1, SP2, SP3, SP4) targeting CD19 antigen were constructed by gene synthesis and molecular cloning technology, and then packaged into lentivirus. The obtained lentivirus was transfected into T cells. The transfection efficiency of the cells was detected by flow cytometry, the killing effect of the cells on target cells was detected by calcein release assay, and the secretion levels of IFN-γ and TNF-α were detected by ELISA. Results: The recombinant lentiviral plasmids with four different SP were successfully constructed, and the four packaged lentiviruses were transduced into T cells. The results showed that 20.76%, 22.29%, 31.57% and 38.42% of T cells expressed CD19-CAR (named as SP1-CD19, SP2-CD19, SP3-CD19 and SP4-CD19 cells, respectively), respectively. The killing effect of SP4-CD19 on CD19- tumor cells was significantly higher compared with SP1-CD19, SP2-CD19 and SP3-CD19 cells (P<0.01), and the secretion levels of IFN-γ and TNF-α in SP4-CD19 cells were significantly higher than those in SP1-CD19, SP2-CD19 and SP3-CD19 cells when the effect-target ratio was 10 to 1 for 24 h (P<0.05). There was no significant difference in the killing effect of CAR-T on CD19 negative cells K562 among four different SP (P>0.05). Conclusion: The transfection efficiency and killing effect of SP4-CD19 cells on CD19+ tumor cells were significantly higher compared with SP1-CD19, SP2-CD19 and SP3-CD19 cells, which laid a scientific foundation for the optimization and efficient clinical application of CAR-T.